Environmental carrying capacity modeling using system dynamics in the context of smart sustainable city: Jakarta case study - Yusuf Kristiadi; Herdis Herdiansyah (Sustainable Urban Development and Environmental Impact Journal, 2024)
Introduction: In Jakarta, rapid urbanization and population increase have led to serious environmental problems such air pollution, water scarcity, and land degradation. Excessive economic activity and population growth are placing pressure on the city's environmental carrying capacity, which is leading to a decline in living standards and an increase in demand on natural resources. Green open space in Jakarta has decreased significantly, currently at 9.8%, below the minimum requirement of 30%. Methods: This study uses a system dynamics approach to assess Jakarta’s environmental carrying capacity in the context of a sustainable city.  Finding: The study shows that Jakarta’s land carrying capacity has decreased since 2018, with indications that water carrying capacity will decrease by 2032 if Jakarta do business as usual. Future scenario suggest that reducing the rate of land turnover and improving water flow will significantly improve the city’s environmental sustainability. For example, reducing land change by 20-40% can restore land carrying capacity by 2040. Conclusion: By implementing policies that focus on reducing land change and improving water infrastructure, Jakarta can improve the quality of life and quality of life for its residents. The novelty of this study is that it integrates the concept of smart sustainable cities with system dynamics modelling to assess environmental sustainability and provides a comprehensive framework that can be adapted by other cities facing similar challenges. The report highlights gaps in current practices, such as the need to better integrate water and green space infrastructure, advanced technologies for water management, and overall land restoration strategies.